(untitled) (Research, Society and Development, 2022)
Bread is a product of daily consumption by most people around the world and for its manufacture it is necessary that several steps take place for the product to be ready. One of them is the biological fermentation that lasts between two to five hours or more for the dough to develop the proper aeration. Aiming to decrease production time of loaf bread, we proposed the development of a bread with chemical fermentation and aqueous extract containing compounds of conventional pan bread flavor. A Central Rotational Composite Design were applied to define the best formulation. The best bread formulation was subjected to analysis of moisture, ash, protein, lipids, carbohydrates, pH, acceptance test and analysis of volatile. The best formulation was the one from the bread made with 8.5% of bread flavoring extract, 7.7% baking powder and 5.5% vegetable fat with a total quality score equal to 73.01%. The breads had a composition in moisture, carbohydrates, proteins and lipids similar to conventional bread with 30,61%, 54.83%, 7.43% and 3.30%, respectively and a higher ash content than conventional bread (3,82%). The acceptance test demonstrated that the evaluators showed the consumption attitude “I would eat it often”. The analysis of the volatiles of fast bread by CG / MS allowed to identify 12 compounds that are part of the flavor of conventional breads. Therefore, we believe in the possibility of making a bread with reduced processing time (< 1,0 hour) and with satisfactory sensory acceptance.